2016
DOI: 10.1109/jsen.2015.2484071
|View full text |Cite
|
Sign up to set email alerts
|

All-Fiber Loading Sensor Based on a Hybrid 45° and 81° Tilted Fiber Grating Structure

Abstract: Abstract-We experimentally demonstrate an all-fiber loading sensor system based on a 45°-and an 81°-tilted fiber grating (TFG). We have fabricated two TFGs adjacent to each other in a single fiber to form a hybrid structure. When the transverse load applied to the 81º-TFG, the light coupling to the two orthogonally polarized modes will interchange the power according to the load applied to the fiber, which provides a solution to measure the load. For real applications, we further investigated the interrogation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Up to now, a considerable amount of optical fiber transverse load sensors have been developed utilizing different fiber devices. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The most common fiber device used to construct the transverse load sensor is fiber grating. Liu et al first reported a long period grating (LPG) in B/Ge co-doped fiber based transverse load sensor.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, a considerable amount of optical fiber transverse load sensors have been developed utilizing different fiber devices. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] The most common fiber device used to construct the transverse load sensor is fiber grating. Liu et al first reported a long period grating (LPG) in B/Ge co-doped fiber based transverse load sensor.…”
mentioning
confidence: 99%
“…In addition, some special FBGs have been used to develop optical fiber load sensors, such as sampled fiber Bragg gratings (SFBGs), 13) chirped fiber Bragg gratings (CFBGs) 14) and tilted fiber gratings (TFGs). 15,16) Recently, Wang et al applied the microwave photonics filtering technique into a FBG sensor for highresolution transverse load measurement. 17) In addition, fiber based interferometers have also been used to measure the transverse load.…”
mentioning
confidence: 99%